PENGARUH DIABETES SELF MANAGEMENT EDUCATION (DSME) TERHADAP SELF-CARE PASIEN DIABETES MELITUS DI RUMAH SAKIT KOTA PALEMBANG - indaryati, sri (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2018)
Diabetes melitus (DM) is a chronic disease that requires self-care. The main problem of health care in Indonesia is the lack of optimalization on the culture of patient self-care. One program that aims to facilitate knowledge and skills for diabetes patients is self-care Diabetes Self Management Education (DSME), that based on independent nursing theory by Orem